AGAINST THE STEREOTYPE OF BLONDE GIRLS IN ROBERT LUKETIC'S LEGALLY BLONDE MOVIE (2001): A SOCIOLOGICAL APPROACH. - SARI, NOVITA (2010)
This study is aimed to show against the stereotype of blonde girls in Legally Blonde movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Legally Blonde movie directed by Robert Luketic released in 2001. While the secondary data sources are other materials taken from books, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on the sociological analysis, there is a close relation between the movie production and the social reality underlying it, such as the negative stereotype of blonde girls. This movie also describes against the stereotype of blonde girl in every aspects.